Polymorphisms in endothelial nitric oxide synthase gene in early and late severe preeclampsia - Alpoim, Patricia Nessralla; Gomes, Karina Braga; Pinheiro, Melina de Barros; Godoi, Lara Carvalho; Jardim, Leticia Lemos; Muniz, Ludmila Gomes; Sandrim, Valeria Cristina [UNESP]; Fernandes, Ana Paula; Dusse, Luci Maria S. (Elsevier B.V., 2014)
Preeclampsia (PE) is characterized by hypertension and proteinuria, occurring after the 20th week of pregnancy in women who have had no previous symptoms. The disease progresses with generalized vasoconstriction and endothelial dysfunction. Clinically, it is important to diagnose the severe form of the disease (sPE), in which blood pressure and proteinuria are much higher. Recently, the gestational age (GA) of the onset of PE has led to the classification of this disease as early (GA <34 weeks) and late (GA >= 34 weeks). Several genetic polymorphisms affecting endothelial nitric oxide synthase (eNOS) levels or function were described, including G894T (Glu298Asp), VNTR b/a (variable-number 27-bp tandem repeat) and T-786C (promoter) polymorphisms. Thus, the aim of this study was to compare the distribution of G894T, VNTR b/a and T-786C polymorphisms and their haplotypes in Brazilian early and late sPE, as well as in normotensive pregnant. A total of 201 women were evaluated, 53 with early sPE, 45 with late sPE and 103 as normotensive pregnant women. The frequency of 894T allele was higher in late sPE vs normotensive pregnant, and 894TT genotype was higher in late sPE vs early sPE and normotensive pregnant. For VNTR b/a polymorphism, higher frequencies of aa genotype and a allele were observed in early sPE vs late sPE and normotensive pregnant. Besides, the frequency of haplotype T-b-C was higher in late sPE vs early sPE and normotensive pregnant. Considering the results found for eNOS polymorphisms, it is possible to suggest that the functional alterations induced by these two polymorphisms may influence the time of severe PE onset, although both alterations are putatively associated with low NO bioavailability. However, other studies are necessary to validate these findings and clarify this issue. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Early/late preeclampsia; Nitric oxide; Polymorphisms; Endothelial nitric oxide synthase gene